(untitled) (Revista de Ciências Agroveterinárias, 2006)
The Living Pharmacies Project is a pharmaceutical social program of attendance to local comunities. It supplies selected, effective and safe medicinal plants and gives orientation to recognise the right especies, learn how to prepare teasor simple pharmaceutical preparations with its own plants. Its aim is to substitute gradually, in the Northeast of Brazil, the uneffective and harmful home-made practices, by the right plants pr oduced in decentralized operational units, endowed with trained personnel. Each unit has a small medicinal garden and a simple pharmaceutical laboratory. The pharmaceutical preparations are so or more effective and safe than the medicines of industrial origin. This model is compatible with the norms of the national politics of medicinal plants and phytotherapics, recently ap proved for the Federal Government and can be accepted by the Brazilian unic system of heath.